Managing the energy transition - the road to a green economy without losers - Ristić, Zoran; Čelik, Petar (Industrija, 2024)
The transition towards a low-carbon economy over the next few decades poses a global challenge, including for Serbia. In regions whose economic development relies on mining (exploitation of non-renewable sources of energy and raw materials), there is a crucial need for investments in new sources of clean energy, the development of new industries, and the creation of new green jobs. Anticipating these trends and their impact on existing mine workers is essential for effectively managing the energy transition and creating a green economy where they won't be left behind. The authors of this paper focus on analyzing the attitudes of mine workers in Serbia regarding this issue and their readiness to embrace changes, aiming to contribute to the promotion of the need for an accelerated and fair energy transition. To ensure the relevance of the conclusions, field research was conducted during November and December 2023, coupled with an analysis of available literature and officially accessible public documents related to this field. Efficient management of the energy transition requires aligning strategies for reindustrialization, innovation, the adoption of clean technologies, and investments in green infrastructure. Simultaneously, measures ensuring a smooth transition are necessary, including social protection, training for acquiring new knowledge and skills, labor market policies, as well as community development and renewal.Keywords: just energy transition, green economy, renewable sources.